Adaptation of Hidden Markov Model in handwriting learning number system to assist preschool children handwriting - Saad, Mohd Nizam; Abdul Razak, Abd Hadi; Yasin, Azman (Universiti Utara Malaysia, 2011)
Nowadays, there are many handwriting recognition systems (HRS) that can be occupied to assist children in learning how to write properly.However, one of the major barriers of the system is its user interface complexity where the design is mostly based on adult preference.In order to solve this problem, we discovered the user interface guidelines proposed by Read (2005) on implementing a HRS interface for children.In this study, we have designed and developed a HRS prototype named Handwriting Learning Number (HLN).The prototype manages to assist the preschool children in learning to write numbers and improving their handwriting skills.Based on the pre and post handwriting test, it is agreed that the system has improved the children handwriting.Apart from that, observation done by us also found that the preschool children’ handwriting on paper have shown a lot of improvement.